WORKFORCE GREENING THROUGH SUPERVISORY BEHAVIOR AND EMPLOYEES’ SUSTAINABLE BEHAVIOR. THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT - Ali, Mr. Qamber; Zaighum, Isma; Dr. Mubashir (The journal of contemporary issues in business and government, 2021)
Managers’ supervisory behavior plays a crucial role in the employees’ sustainable behavior of any type of officialdoms. Affirmative sustainable behavior augments all the indicators of the performance in an organization. Therefore, this study aims to investigate the collective effect of supervisory support, trust in the supervisor, and having a commitment to the supervisor for forecasting the sustainable behavior of employees working in banking sectors in Pakistan. This study also investigated the mediating role of employees’ organizational commitment on the relationship between supervisory behaviors and employees’ sustainable behavior. The data were collected frombankers working in various commercialbanks in Pakistan through convenience sampling. A total of 387 valid questionnaires were received and analyzed through Partial Least Square Structural Equation Modelling (PLS-SEM). The findings of the study show that supervisory behavior has a significant positive impact on employee sustainable behaviors.Supervisory behavior (ESS, ISB, TS, and CS) have a significant direct effect on the employees’ organizational commitment. Further, findings also confirmed that employees' organizational behavior mediates the relationship between supervisory behavior (ESS, ISB, TS, and CS) and employees' sustainable behavior. The study enhances the existing literature and provides useful insights to supervisors working in banks, and helps to improve employees’ sustainable behavior.